Comparison of peptide peak intensity methods for label free relative protein quantification - Namvar Tehrani, Nima (fi=Turun yliopisto|en=University of Turku|, 2018)
During the recent years, Liquid chromatography-mass spectrometry (LC-MS) has gained enormous attention to identify and quantify peptides in biological samples. The Current challenge is to quantify the level of proteins as well as identifying them. Recently several computational approaches for protein quantification based on measured peptides have been introduced. The aim of this study is to delve into most commonly employed approaches to estimate relative protein abundance from peak intensity values and have a comparison between different methods.